Climate resilient pathway for developing nations : case study of electric vehicle market in Nepal - Pandey, Abarta (2019)
The IPCC Special report emphasized the climate crisis we are heading towards exceeding the 1.5-degree limit at the current path. All the emerging reports suggest that we are not doing enough to transform our economy and society to fight the ongoing climate crisis. In the next decades, this crisis is bound to be more challenging with developing economies striving towards economic development. Hence, this reflects the urgent need for the climate resilient pathway for development. One of the main sectors with available alternative technology is the transportation sector which has a huge potential to curb the GHG emissions. The transportation sector directly accounted for 14% of the total GHG emissions in the world in 2014 excluding the energy use and its corresponding GHG emissions. The availability and accessibility of Electric Vehicles all around the world is a positive indication to strive towards zero emission mobility. The developing nations are at a crucial point in the fight against climate change as they are striving towards economic growth. The role of all stakeholders is crucial in this change from governments to consumers. The research is carried out on consumers from the least developed and land locked South Asian nation of Nepal to understand the consumer behaviour towards Electric Vehicles. The survey reflected a hidden demand for the EV automobile market in Nepal with lack of implemented government policies, lack of EV infrastructure and also the lack of supply of EVs as major obstacles to carry out the transformation. The research also highlights the lack of active population to initiate the transformation of the market with the huge problem due to the ongoing brain drain in the developing nations. The research concludes with lack of government coordination, and efforts to introduce and implement the policies to move towards the climate resilient pathway towards development. This is especially tricky for developing nations as they must omit short term economic gains hence requiring added international financing to execute these transformations.